Isolasi dan Uji Aktivitas Enzim Superoksida Dismutase (SOD) dari Bakteri Endofita Daun Tanaman Sukun (Artocarpus altilis) dengan Metode Water Soluble Tetrazolium Salt-1 (Wst-1) - Fradine, Chossy; Wulandari, Destik; Purwaningsih, Desi (Herbal Medicine Journal, 2025)
Endophytic bacteria are bacteria that carry out symbiosis with host plants without causing disease without the host plant. Some endophytic bacteria found in plants are able to produce potential compounds as antioxidants by producing the enzyme SOD (Super Oxide Dismutase). This research aims to determine the results of endophytic bacterial fermentation from the leaves of the breadfruit plant (Artocarpus altilis). This research began with the identification of endophytic bacteria, then continued with the extraction of the SOD enzyme by adding PBS and centrifuging. Purification of the SOD enzyme was carried out using the ammonium sulfate precipitation method. Determination of total protein content using the Lowry method. SOD activity was measured by measuring the percent inhibition value using the Superoxide Dismutase Activity Assay Kit WST-1. The results of the research showed that the isolated bacteria had morphological characteristics in sequence from colony shape, color, size, elevation, edges, cell shape and Gram type for AL 4 bacteria Filamentous, white, medium, flat, Rhizoid, coccus, Gram +, citrate -, Catalase -, for IL11 bacteria Irregular, white, large, flat, entire, bacilli, and Gram +, citrate +, Catalase +. The extraction results from the crude extract produced a sediment weight of 2,915 g for AL4 and 1,653 g for IL11. The total protein content of the crude extract and 30% ammonium sulfate precipitation for isolate AL4 was 1.74 mg/mL and IL11 1.79 mg/ml. Then the percent inhibition value for isolate AL4 with a concentration of 20% was 64.02% and a concentration of 80% was 71.43%.